Mapping debris flow susceptibility based on watershed unit and grid cell unit: a comparison study. Issue 1 (1st January 2019) - Qin, Shengwu; Lv, Jiangfeng; Cao, Chen; Ma, Zhongjun; Hu, Xiuyu; Liu, Fei; Qiao, Shuangshuang; Dou, Qiang
Abstract: Debris flow susceptibility analysis is a prerequisite of risk assessment. The main objective of this study was to explore the accuracy and practicability of mapping units for evaluation of debris flow susceptibility. These units include grid cell units (GCUs), and watershed units (WUs) with the flow thresholds 10 000 (WU 10 000) and 5000 (WU 5000). The frequency ratio (FR) model was selected as the statistical method. Yongji County (YJC) of Jilin Province, China was selected as the research site, and a total of 123 debris flow disasters were surveyed. Eight influencing factors were considered and a total of three models were constructed. The predictive capabilities of the models were verified using an ROC curve and AUC. The results showed the three models to be accurate and the evaluation results of the GCU were found to be more accurate than others. However, when considering the effects of geology and geomorphology on the occurrence of debris flows, the WU was more feasible than the GCU. Therefore, the results indicate that the evaluation of debris flow susceptibility should be carried out based on the WU of the appropriate flow threshold in combination with the actual prevention and control of debris flow disasters.